The Effects of School Consolidation on Student Academic Achievement in High-Resource Urban Schools - Kseniia Adamovich; Aleksandra Getman; Anastasiia Kotlikova (Экономическая социология, 2025)
School consolidation is often viewed as a strategy for improving educational quality while staying within budget constraints. This paper investigates the impact of school consolidation on student academic achievement in the context of high-resource urban schools, contributing to the ongoing discourse on the interaction between school size and students’ socioeconomic status (SES). Using a quasi-experimental approach, the study analyzes data from 6,473 Moscow schools and their consolidations between 2013 and 2019. The findings reveal a U-shaped relationship between school size and student performance on the Basic State Examination: the highest achievement is observed in both the smallest and largest schools. The overall effect of consolidation on exam performance is slightly negative, suggesting that further consolidation may not significantly benefit schools with already sufficient resources. The timing of consolidation is critical — earlier consolidations are associated with lower student achievement compared to those implemented later. A negative shock in academic performance is also observed in the year immediately following consolidation; however, no delayed positive effects are detected within the observation period. These results contribute to the policy debate on the effectiveness of school consolidation and highlight the importance of considering school size, SES, and implementation timing when assessing their influence on student outcomes. Further research is recommended to examine consolidation’s effects on elective subjects and to assess its long-term consequences.